4(x-1)=2x+1

Simple and best practice solution for 4(x-1)=2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)=2x+1 equation:


Simplifying
4(x + -1) = 2x + 1

Reorder the terms:
4(-1 + x) = 2x + 1
(-1 * 4 + x * 4) = 2x + 1
(-4 + 4x) = 2x + 1

Reorder the terms:
-4 + 4x = 1 + 2x

Solving
-4 + 4x = 1 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-4 + 4x + -2x = 1 + 2x + -2x

Combine like terms: 4x + -2x = 2x
-4 + 2x = 1 + 2x + -2x

Combine like terms: 2x + -2x = 0
-4 + 2x = 1 + 0
-4 + 2x = 1

Add '4' to each side of the equation.
-4 + 4 + 2x = 1 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = 1 + 4
2x = 1 + 4

Combine like terms: 1 + 4 = 5
2x = 5

Divide each side by '2'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| -2a-9=36 | | 42m^3-36m^2-49m+42=0 | | 8x^2+5x+k=0 | | y^2+33=-8x-23 | | 3x^2+16x=-21 | | (n+11)n=84 | | 3=-16t^2+19t+0 | | 54a^2-144a=0 | | 2x^2-42=8 | | 2+3(n-6)=4(n+2)-21 | | 20x-8-12x+3=21x-9-13x+14 | | 15(-4g+8)+6=-1-(9-8g) | | 5p+14=8p(-2) | | 60n^2+258n+168=0 | | 2X^3-3X^2-3=0 | | 5.3x-3.24=3.18-5.4x | | 5p+14=8p-(-2) | | -3x+3=-33 | | 2.1x-5.25=3.15-3.5x | | 9x+7=6x+8 | | 2.1x-5.25=3.15-3.5 | | -7x-12+20x=14-12x+25x-10 | | 5x^2+46x-40=0 | | 3n+7=5n+3 | | 9x+5y=11x-8y | | 3x-5+1=-2x+7 | | 7+9(x-3)=1-6(x-9) | | 9y+5x=11y-8x | | 6y+5=11y+30 | | (-12a)(ab)=0 | | 18x^2-72x+40=0 | | (-12abc)(4ab)=0 |

Equations solver categories